AN ANALYSIS OF ENGLISH INTERFERENCE INTO INDONESIAN LANGUAGE USED IN TALK SHOW “HITAM PUTIH” AT TRANS 7 - Samsul Maulana Hasanudin (IKIP Siliwangi, 2018)
The objectives of the research entitled “An Analysis of English Interference into Indonesian Language Used in Talk Show HitamPutih at Trans 7” were to find out how many English Interference, what types of Interference the most frequently used, and to find out what types of interference the least frequently used by the article writer. The writer used descriptive qualitative method. The instrument used to collect the data were the pieces of paper covering the types of English Interference. The populations were all the texts of sport article issued since 5th – 16th March 2013, and the sample of this research was entire population. The data of the research were collected, by reading all the text (10 sport articles) Media Indonesia Daily Newspaper, the collected data were identified, classified, analyzed and interpreted. The results of this research showed that: The article writer used 174 words of English Interferences. They were divided into four types: phonetic interference (3 words: 5,08%), grammatical Interference (6 words: 10,7%), lexical interference (10 words: 16,94%) and semantic interference (40 words: 67,79%). Based on the data analysis, the most English interference frequently used by the article writer was English Semantic interference and the least frequently used were phonetic interference.